CYP3A and CYP2C19 activity in urine in relation to CYP3A4, CYP3A5, and CYP2C19 polymorphisms in Russian peptic ulcer patients taking omeprazole - Denisenko NP; Sychev DA; Sizova ZM; Smirnov VV; Ryzhikova KA; Sozaeva ZA; Grishina EA (Dove Medical Press, 2018)
Natalia P Denisenko,1–3 Dmitriy A Sychev,2 Zhanna M Sizova,3 Valeriy V Smirnov,4,5 Kristina A Ryzhikova,1 Zhannet A Sozaeva,1 Elena A Grishina1 1Research Center, Russian Medical Academy of Continuous Professional Education, Ministry of Healthcare, Moscow, Russia; 2Department of Clinical Pharmacology and Therapy, Russian Medical Academy of Continuous Professional Education, Ministry of Healthcare, Moscow, Russia; 3Department of Social Expertise, Urgent and Outpatient Therapy, First Moscow State Medical University (Sechenov University), Ministry of Healthcare, Moscow, Russia; 4Department of Pharmaceutical and Toxicological Chemistry, First Moscow State Medical University (Sechenov University), Ministry of Healthcare, Moscow, Russia; 5Laboratory of Clinical Pharmacology, National Research Centre – Institute of Immunology, Federal Medical Biological Agency, Moscow, Russia Background: Proton pump inhibitors (PPIs) are metabolized by cytochrome P450. CYP2C19 is the main isoenzyme for the majority of PPI, whereas CYP3A family is a secondary enzyme for PPI biotransformation. Purpose: The aim of the study was to find if CYP3A4*22, CYP3A5*3, CYP2C19*2, CYP2C19*3, and CYP2C19*17 genotypes are connected with CYP3A and CYP2C19 activities in Russian peptic ulcer patients taking omeprazole. Patients and methods: Forty-eight gastric or duodenal ulcer patients (15 men, 33 women; mean age 55.0±15.3 years, age range 18–91 years) from Moscow region of Russia were enrolled. Peripheral venous blood was collected for DNA extraction, and real-time polymerase chain reaction was performed for CYP3A5*3 A6986G (rs776746), CYP3A4*22 C>T in intron 6 (rs35599367), CYP2C19*2G681A (rs4244285), CYP2C19*3G636A (rs4986893), and CYP2C19*17C-806T (rs12248560) polymorphism analyses. Urine samples of patients were collected in the morning between 6 and 9 am before food or drug intake. Urine cortisol and 6β-hydroxycortisol concentrations (for CYP3A activity) and omeprazole and 5-hydroxyomeprazole concentrations (for CYP2C19 activity) were measured using high-performance liquid chromatography/mass spectroscopy. Results: We found a connection between CYP2C19 genotypes and CYP3A activity. Median metabolic ratios 6β-hydroxycortisol/cortisol (25%–75% percentiles) were 2.84 (1.99–4.39) for CYP2C19 extensive metabolizers (EMs), 2.51 (1.86–4.73) for CYP2C19 ultra-rapid metabolizers (UMs), and 1.45 (1.12–2.16) for CYP2C19 intermediate metabolizers (IMs) + poor metabolizers (PMs). A statistically significant difference in CYP3A activity (Mann–Whitney test) was found between CYP2C19 EMs vs CYP2C19 IMs+PMs (p=0.006), between CYP2C19 UMs vs CYP2C19 IMs+PMs (p=0.018), and in multiple comparison Kruskal–Wallis test (p=0.014). Conclusion: In CYP2C19 IMs+PMs, CYP3A activity was significantly lower than in CYP2C19 EMs and UMs. Keywords: pharmacogenetics, phenotyping, metabolomics, proton pump inhibitor